SISTEM KONTROL SUHU PENYIMPAN BUAH-SAYUR PADA MESIN PENDINGIN TERMOELEKTRIK - Aziz, Rofan; Afkar, Muh Tanwirul; Sunanto, Sunanto; Karsid, Karsid (P3M Politeknik Negeri Indramayu, 2017)
Conventional cooling systems based on vapor compression have a high coefficient of performance (COP). However shortage of vapor compression cooling systems still using refrigerants that have detrimental effects on the environment. For that purpose, the research of fruit and vegetable storage machine using thermoelectric system TEC1-12706 with temperature control system using arduino. In this study the temperature in the cabin can be stable at 15° C and still feasible for use as a storage of fruits and vegetables.